Is pathological complete response predictable after neoadjuvant chemotherapy in breast cancer? A single institution's retrospective experience. Issue 9 (31st May 2021) - Winder, Alec A.; Dijkstra, Birgit
Abstract : Retrospective review of radiological and pathological response to neoadjuvant chemotherapy. Can magnetic resonance imaging be used to predict complete pathological response? A single institutional retrospective case series. Abstract: Background: Pathological complete response (pCR), in breast cancers, after neoadjuvant chemotherapy is linked to improved survival. Determining complete response to chemotherapy prior to surgery has remained elusive even using a combination of pathological factors and imaging modalities, making surgery still a necessity. Methods: A retrospective analysis was performed from a single institution from 2013 to 2018. Breast cancer patients treated with neoadjuvant chemotherapy with pre‐ and post‐chemotherapy magnetic resonance imaging (MRI) were included. Patients receiving other neoadjuvant modalities were excluded. Imaging characteristics, including response to chemotherapy and pathological factors, were recorded. Results: Analysis showed 134 patients were identified with 40/134 (29.9%) noted to have radiological complete response and 34/134 (25.6%) had pCR. The positive predictive value for MRI to detect pCR was greatest for oestrogen receptor (ER) negative and human epidermal growth factor receptor 2 (HER2) negative tumours at 81.8% and worst for ER+ HER2− tumours at 25%. The negative predictive value was greatest for ER+ HER2− tumours at 93.9% and worst for ER− HER2− tumours at 77.4%. Conclusion: MRI after neoadjuvant chemotherapy for breast cancer even combined with tumour factors is not an accurate predictor of pCR.